Análisis del Sistema de Control Interno y su efecto en la gestión de los inventarios de la empresa NOVAOPTICUM, de la ciudad de Manta. - Salcedo Alcívar, Maideline María (2023)
The purpose of this research project is to investigate the internal control system and its effect on the management of inventories of the company NOVAOPTICUM S.A, from the city of Manta, in order to identify how the management of functions is determined within the departments involved in the institution. The optics presents a deficit within internal control, resulting in the constant loss of merchandise, since the staff is not aware of the operation and activity that they must carry out. Having as main objective to propose a design of internal control system according to the needs presented in the inventory management for the correct operation of the business, which allows to improve the efficiency in decision making. The research methods used were analytical,